2016
DOI: 10.1007/s00403-016-1646-7
|View full text |Cite
|
Sign up to set email alerts
|

S100A8/A9 is an important host defence mediator in neuropathic foot ulcers in patients with type 2 diabetes mellitus

Abstract: Chronic wounds and in particular diabetic foot ulcers (DFUs) are a growing clinical challenge, but the underlying molecular pathophysiological mechanisms are unclear. Recently, we reported reduced levels of the immunomodulating and antimicrobial S100A8/A9 in non-healing venous leg ulcers (VLUs), while another study found increased S100A8/A9 in DFUs. To clarify these apparently contradictory findings, we compared S100A8/A9 as well as an inducer, lipopolysaccharide (LPS) and selected innate immune response media… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
45
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 28 publications
(46 citation statements)
references
References 37 publications
1
45
0
Order By: Relevance
“…In a recent clinical study, our group found a correlation between levels of lipopolysaccharide and VEGF in chronic wounds fluids . Tissue hypoxia strongly induces VEGF levels .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In a recent clinical study, our group found a correlation between levels of lipopolysaccharide and VEGF in chronic wounds fluids . Tissue hypoxia strongly induces VEGF levels .…”
Section: Discussionmentioning
confidence: 99%
“…We previously reported reduced levels of S100A8/A9 in non‐healing human and in infected murine chronic wounds . The present study supports the suppressing effect of P. aeruginosa biofilm on host level of S100A8/A9, especially located towards the centre of the wounds at the earliest point of the evaluation stages (4 DPI).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…S100A8/A9 has wide antifungal and antimicrobial potential [ 8 ]. We previously reported reduced S100A8/A9 levels in colonized human chronic wounds [ 9 , 10 ]. Since P. aeruginosa is able to degrade cytokines [ 11 ], S100A8/A9 may likewise be degraded in vivo in anatomically close proximity to the P. aeruginosa biofilm as part of the evasion of the immune system.…”
Section: Introductionmentioning
confidence: 99%
“…27 If the fundamental disposing factor is not corrected, the colonization will proceed to the establishment of a permanent state of biofilm infection ultimately perturbing and impairing the host response. [28][29][30] Microbes gaining access to exposed subcutaneous fatty tissue will be able to cause local infection as the mature biofilm is resistant to host response and antimicrobial therapy. 29 Human comorbidity such as systemic disease with chronically elevated inflammatory markers, malnutrition, fluctuating glucose levels, or neuropathies is a conducive microenvironment for a biofilm establishment.…”
Section: Establishment Of a Chronic Wound Environmentmentioning
confidence: 99%